2020
DOI: 10.1186/s13063-020-04565-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative individualized PEEP on postoperative atelectasis in obese patients: study protocol for a prospective randomized controlled trial

Abstract: Background: Obese patients undergoing general anesthesia and mechanical ventilation during laparoscopic abdominal surgery commonly have a higher incidence of postoperative pulmonary complications (PPCs), due to factors such as decreasing oxygen reserve, declining functional residual capacity, and reducing lung compliance. Pulmonary atelectasis caused by pneumoperitoneum and mechanical ventilation is further aggravated in obese patients. Recent studies demonstrated that individualized positive end-expiratory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The appropriate positive end-expiratory pressure (PEEP) application might prevent intraoperative atelectasis, but not after extubation [ 22 ]. Here, obese patients may benefit from an intraoperative individualized PEEP [ 23 ]. Furthermore, a randomized clinical trial shows that the choice of an intraoperative high PEEP level combined with alveolar recruitment maneuvers is not associated with a reduction of postoperative pulmonary complications compared to an intraoperative lower PEEP level in obese patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate positive end-expiratory pressure (PEEP) application might prevent intraoperative atelectasis, but not after extubation [ 22 ]. Here, obese patients may benefit from an intraoperative individualized PEEP [ 23 ]. Furthermore, a randomized clinical trial shows that the choice of an intraoperative high PEEP level combined with alveolar recruitment maneuvers is not associated with a reduction of postoperative pulmonary complications compared to an intraoperative lower PEEP level in obese patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are associated with postoperative pulmonary complications (PPCs). It seriously affects the postoperative outcome in surgical patients [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researches have shown that PCV-VG provides lower airway pressure and better lung mechanics and exerts a huge potential lung-protective effect in various fields [8][9][10]. Additionally, numerous studies also showed that lung mechanics and gas exchange can be improved by the application of PEEP [10][11][12][13]. However, it was unreasonable to apply a fixed PEEP for all patients, and it is critical to determine individualized PEEP by the "titration method" to stabilize the lung function and minimize lung injury, thereby contributing to preferable physiologic and lung-protective effects [10,14].…”
Section: Introductionmentioning
confidence: 99%